1998
DOI: 10.1074/jbc.273.18.11164
|View full text |Cite
|
Sign up to set email alerts
|

Inability of the Acidic Fibroblast Growth Factor Mutant K132E to Stimulate DNA Synthesis after Translocation into Cells

Abstract: Acidic fibroblast growth factor (aFGF) is a potent mitogen. It acts through activation of specific cell surface receptors leading to intracellular tyrosine phosphorylation cascades, but several reports also indicate that aFGF enters cells and that it has an intracellular function as well. The aFGF(K132E) mutant binds to and activates fibroblast growth factor receptors equally strongly as the wild-type, but it is a poor mitogen. We demonstrate that aFGF(K132E) enters NIH 3T3 cells and is transported to the nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
87
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(91 citation statements)
references
References 40 publications
4
87
0
Order By: Relevance
“…U2OSDr1-R4 cells, a human osteosarcoma cell line stably transfected with FGFR4, bind aFGF and transport the growth factor to the nuclear fraction (14,18,63). The results in Fig.…”
Section: Fig 1 Effect Of Pi-3 Kinase Inhibitors On Binding (A and Bmentioning
confidence: 68%
See 4 more Smart Citations
“…U2OSDr1-R4 cells, a human osteosarcoma cell line stably transfected with FGFR4, bind aFGF and transport the growth factor to the nuclear fraction (14,18,63). The results in Fig.…”
Section: Fig 1 Effect Of Pi-3 Kinase Inhibitors On Binding (A and Bmentioning
confidence: 68%
“…We recently demonstrated that aFGF contains a functional phosphorylation site for protein kinase C (18,73) and that the growth factor can be phosphorylated at this site upon incubation with COS cells transfected with functional FGFR4. 2 In this paper we use phosphorylation of aFGF as a measure of translocation to the cytosol and nucleus, since these are the only places in the cell where protein kinase C is known to exist.…”
Section: S]methionine-labeled Afgf (Upper Panel) As Well As Farnesylamentioning
confidence: 99%
See 3 more Smart Citations